2014
DOI: 10.1007/8904_2014_313
|View full text |Cite
|
Sign up to set email alerts
|

Sports in LCHAD Deficiency: Maximal Incremental and Endurance Exercise Tests in a 13-Year-Old Patient with Long-Chain 3-Hydroxy Acyl-CoA Dehydrogenase Deficiency (LCHADD) and Heptanoate Treatment

Abstract: Exercise and subsequent catabolism is a potential trigger for creatine kinase (CK) concentration increase (rhabdomyolysis) in patients with LCHADD, therefore we evaluated the clinical and biochemical stability under physical exertion conditions at the age of 13 years in a currently 14-year-old LCHADD patient treated with heptanoate.LCHADD was diagnosed during first decompensation at age 20 months. In the following 2 years, the patient had several episodes of rhabdomyolysis. Heptanoate 0.5-1 g/kg/day was starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Other important health activities that maintain LBM include normal routine exercise. Many patients with LC‐FAOD report muscle pain and lethargy with exercise and can become increasingly more sedentary over time . Disuse muscle atrophy would be expected to affect both LBM and the ability to maintain activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other important health activities that maintain LBM include normal routine exercise. Many patients with LC‐FAOD report muscle pain and lethargy with exercise and can become increasingly more sedentary over time . Disuse muscle atrophy would be expected to affect both LBM and the ability to maintain activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with LC-FAOD report muscle pain and lethargy with exercise and can become increasingly more sedentary over time. 1,31 Disuse muscle atrophy would be expected to affect both LBM and the ability to maintain activities of daily living. We did not measure participant activity in this study, so we cannot report whether these differences in LBM between the diet groups was able to close the "activity gap" in TEE of participants with LC-FAODs compared to normal controls that we have previously hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…triheptanoin, has played an important role (10), even though its mode of action at a cellular level is still under investigation (17). However, even though triheptanoin treatment renders promising results in clinical practice (14,15), the challenge to quantify its effect in patients remains as reliable biochemical markers are lacking. Thus, surrogate markers are chosen to show bene cial effects of triheptanoin, like hospitalization needed before and after initiation of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach to triheptanoin therapy resulted from a rst very positive experience with the oil in Patient over 15 years ago (14,15). As the initial preparation was an industrial oil that was used as an anticorrosive and was not very palatable and quite aggressive to plastic materials, after trying it ourselves and with informed consent of the parents of Patient 1 we started with an initial dosing of 0.5 g/kg/d.…”
Section: Discussionmentioning
confidence: 99%
“…A second study in 11 patients showed a lower steady state heart rate at the same workload after using pre-exercise MCT supplementation (0.5 g/kg lean body mass) compared to isocaloric carbohydrate supplementation in long chain fatty acid oxidation disorders (Behrend et al 2012). In addition, a positive effect of an odd chain triglyceride, triheptanoate, on exercise performance in a single LCHADD patient has been reported (Karall et al 2014). Since no cardiac output measurements were performed, these studies cannot distinguish between a positive effect of MCTs at the level of the heart versus the skeletal muscle.…”
Section: Introductionmentioning
confidence: 97%